Handbook of farm, dairy, and food machinery engineering - Kutz, Myer (Academic Press, 2019)
Handbook of Farm, Dairy, and Food Machinery Engineering, Third Edition, is the essential reference for understanding the food industry, from farm machinery, to dairy processing, food storage facilities and the machinery that processes and packages foods.